Russia Monthly Economic Developments, July 2015 - Hans, Birgit; Baffes, John; Emelyanova, Olga; Ulatov, Sergei; Vashakmadze, Ekaterine (World Bank, Washington, DC, 2015)
In June, the European Council extended EU economic sanctions against Russia for another six months while Russia extended its food import ban against Western countries for a year. A fluid situation on global financial markets and yet again lower growth prospects led to oil prices losing ground in early July. Ruble depreciation pressure remained throughout June as demand for foreign currency increased while supply declined slightly due to lower oil prices. Russia’s first quarter GDP growth was revised from -1.9 to -2.2 percent−still slightly less than projected earlier−while May high frequency statistics show a deepening recession. On June 25, the government approved the main parameters for the 2016–2018 budgets, foreseeing persistent deficits and evaporating fiscal buffers despite significant expenditure cuts.